The Burden of Care: Mothers' Experiences of Children with Congenital Heart Disease - Sakinne Sabzevari; Monirsadat Nematollahi; Tayebeh Mirzaei; Ali Ravari (Shiraz University of Medical Sciences, 2016)
Background: Mothers play a key role in caring for their sick children. Their experiences of care were influenced by culture, rules, and the system of health and care services. There are few studies on maternal care of children with congenital heart disease. Also, each of them has studied a particular aspect of care. The present research aimed to understand care experiences of mothers of children with congenital heart disease. Methods: A conventional content analysis was used to obtain rich data. The goal of content analysis is "to provide knowledge and deeper understanding of the phenomenon under the study". The study was conducted in Kerman, Iran in 2014, on mothers of children with CHD. The purposive sampling technique was used to select the participants. Participants were 14 mothers of children with CHD and one father and one nurse of open heart surgery unit, from two hospitals affiliated with Kerman University of Medical Sciences. Eighteen semi-structured interviews were constructed. Data were analyzed using conventional content analysis. MAXQDA 2007 software (VERBI GmbH, Berlin, Germany) was used to classify and manage the coding. Constant comparative method was done for data analysis. The reliability and validity of the findings, including the credibility, confirm ability, dependability, and transferability, were assessed. Results: According to the content analysis, the main theme was the catastrophic burden of child care on mothers that included three categories: 1) the tension resulting from the disease, 2) involvement with internal thoughts, and 3) difficulties of care process Conclusion: The results of this study may help health care professionals to provide supportive and educational packages to the patients, mothers and Family members until improving the management of patient's care.